Efficacy of sacral neuromodulation in treating chronic pain related to painful bladder syndrome/interstitial cystitis in adults - Devjit Srivastava (Wolters Kluwer Medknow Publications, 2012)
Objective: The objective of this review is to evaluate the efficacy and safety of sacral neuromodulation in treating chronic pelvic pain related to Painful bladder syndrome/Interstitial-cystitis. Design: The databases searched were MEDLINE and EMBASE [1950- Nov 2011]. Additional searches were performed on the Cochrane Database of Systematic reviews (CDSR), Scopus, CINAHL, BIOSIS, The Cochrane controlled trials register, the science citation index, TRIP DATABASE. Results: Overall 70.8% or 170/244 patients were successful at the trial stage. The only randomized controlled trial reported a decrease in Visual analogue pain scores of 49% (7.9 to 4.0) for sacral nerve stimulation [SNS] and 29%(4.5 to 3.2) for pudendal nerve stimulation [PNS] at 6 months follow up. Nine observational studies reported a decrease in pain scores/decrease in pain medications at long term follow up following permanent sacral neuromodulation. One study showed an 80% improvement in Global response assessment score. Conclusion: The results from the randomised controlled trial and case series/case reports demonstrate a reduction of pain symptoms of Painful bladder syndrome following sacral neuromodulation